2011
DOI: 10.3109/00016357.2011.568962
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of primary root caries lesions after daily intake of milk supplemented with fluoride and probiotic lactobacilli in older adults

Abstract: Daily intake of milk supplemented with fluoride and/or probiotic bacteria may reverse soft and leathery PRCL in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 25 publications
4
68
1
4
Order By: Relevance
“…This is supported by certain study (22) which proved that daily consumption of milk and dairy products may reverse soft and leathery caries and decrease the salivary level of SM in adults.…”
Section: Discussionsupporting
confidence: 55%
“…This is supported by certain study (22) which proved that daily consumption of milk and dairy products may reverse soft and leathery caries and decrease the salivary level of SM in adults.…”
Section: Discussionsupporting
confidence: 55%
“…Other investigations have explored the potential role for probiotic lactobacilli and bifidobacteria to modulate the oral microbial ecology [67]. Data have indicated that regular intake of milk supplemented with probiotic lactobacilli and fluoride dramatically reduces dental caries in children and adults [68]. Results from laboratory and animal model studies are promising; however, largescale, randomized clinical trials are still needed to support the utilization of probiotics as a safe and long-lasting treatment for dental caries.…”
Section: Cariogenic Biofilmmentioning
confidence: 88%
“…In another double-blind, placebo-controlled trial of milk supplemented with fluoride and/or L. rhamnosus the effect on primary root caries lesions was investigated. The use of milk only supplemented with lactobacilli showed a positive effect, as well as the fluoride, but the beneficial effect was strongest by combining both [76].…”
Section: Thereforementioning
confidence: 99%